Optimizing international otolaryngology service trips: Perceptions from learners versus volunteers. (30th July 2019) - Worden, Cameron P.; Stephenson, Elizabeth D.; Senior, Brent A.
Abstract : Objectives/Hypothesis: Optimizing value of medical service trips (MSTs) requires alignment of the services provided with the needs and desires of hosts. Our aim was to understand which MST services Vietnamese otolaryngologists find most beneficial and contrast to those believed most important by volunteers. Study Design: Cross‐sectional survey. Methods: Otolaryngologists from a tertiary care institution travel to Vietnam yearly. In March 2018, surveys were distributed to Vietnamese otolaryngology faculty, residents, and US otolaryngology volunteers. The value of 11 MST‐provided services were graded on a five‐point Likert scale. Services included observing US otolaryngology volunteers perform surgery, US otolaryngology volunteer lectures, paper/electronic lecture material, instrument donation, minifellowships in the United States, among others. Respondents also voted for the single most important service. Responses were analyzed via Kruskal‐Wallis analysis of variance and Wilcoxon rank sum test. Results: A total of 153 survey responses were recorded. There were 52% respondents who identified as male and 39% as female. The highest‐valued services by Vietnamese otolaryngologists were didactic lectures given by US otolaryngology volunteers (4.6/5 ± 0.6), and reviewing cases with US otolaryngology volunteers in the clinic (4.4/5 ± 0.9). The least important services were instrument donation and seeing US otolaryngology volunteers assist with surgery (≤4.1/5). The highest‐value services perceived by US otolaryngology volunteers were reviewing cases in the clinic and sponsoring minifellowships (4.9 ± 0.4). Vietnamese faculty perceived the single most important service to be US volunteer lectures (20/74 votes), whereas Vietnamese residents perceived minifellowships to be most important (13/34 votes) Conclusions: Vietnamese otolaryngologists desire an education‐focused relationship with US otolaryngology volunteers, with didactic lectures and sponsored US fellowships having the highest value and performance of surgeries having less value. Level of Evidence: 4 Laryngoscope, 130:E305–E310, 2020